STRATEGI INOVASI DALAM MEMPERTAHANKAN EKSISTENSI PRODUK UMKM DI MASA PANDEMI COVID-19 - Erina Sovania (Universitas Kadiri, 2022)
The purpose of this community service is to provide an understanding of innovation strategies in marketing amid the covid-19 pandemic. Partners in this service are MSME actors who are in the Alumni Association of SMPN 84 North Jakarta. The main problem faced by partners is the decline in product sales during the Covid-19 pandemic, which has an impact on the motivation and enthusiasm of MSME actors to be confident in their work. The solution offered in this community service is through lectures and discussions supported by practitioners/academics in the field of marketing. The target of this activity is the growth and confidence and optimism in doing business through innovation strategies and product creativity. The method of implementing community service is carried out by giving lectures on training materials and discussions directly delivered by Perbanas Marketing Lecturers. The results stated that the participants were very enthusiastic and liked all kinds of events well, feeling excited to start creative thinking activities on how to make a new product so that consumers would not get bored.